Can the Impact of Company Size Moderate the Connection Between Tax Planning and Company Value? - Wahyuda, Galuh Shinta Hapsari; Ardhani, Lutfi (E-Jurnal Akuntansi; Vol 32 No 8 (2022)DO - 10.24843/EJA.2022.v32.i08.p15, 2022)
A solid company value will give investors confidence that their investment will grow and develop successfully. Firm value is one aspect that investors consider when deciding to invest their money. The benefits of this study are to determine the effect of tax planning on firm value and to determine the effect of firm size on the relationship between tax planning and firm value. The company's management maximizes the value of the company through effective management, which will inspire investors to invest their capital. Companies listed on the Indonesia Stock Exchange (IDX) and included in the 2017-2021 LQ45 rating are the companies used for the research sample. The companies selected as research samples for the LQ45 ranking are 23 companies using purposive sampling method and Moderated Regression Analysis (MRA). The data was then processed using SPSS 26. The relationship between the Tax Planning variable and firm value did not have a significant effect (rejected), according to the findings of hypothesis testing which was tested by the T test. The moderating variable, namely company size, was rejected because it could not strengthen the relationship between Tax Planning and firm value. Keywords: Company Size; Tax Planning; Company Value